Pengenalan Digital Marketing dalam Rangka Meningkatkan Penjualan Hasil Pertanian di Desa Pasar Lembu Kecamatan Air Joman Kabupaten Asahan Provinsi Sumatera Utara - Siti Ummi Arfah Nasution; Zulaili Zulaili; Siti Wardah Pratidina Nst; Winda Wardhani; Zakia Heli Maulana (Pusat Riset dan Inovasi Nasional, 2024)
The development of information technology has brought changes to people's lives, such as the widespread use of smartphones as a circulating digital communication medium and its very rapid development has an impact on society, especially in supporting business activities both on a large and small scale, one of which is the livelihood sector. The increasingly worrying condition of farmers, coupled with the spread of coronavirus disease 2019 (COVID-19) in 2020, has brought changes to the business sector, experiencing very drastic changes and decline. Some countries have implemented lockdowns, there are social restrictions and there are regulations on people's life activities not to gather in crowds, especially in buying and selling activities. With the help of this technology, online systems can help business actors to expand networks between businesses that are no longer limited by barriers of time and space. This outreach activity is very beneficial for the community, most of whom are farmers. The material provided can also increase understanding of knowledge and practice of steps to use Facebook or Instagram for product promotion. Through this outreach activity, it is hoped that it can increase awareness of the farming community and MSMEs in Pasar Lembu Village, Air Joman District, Asahan Regency, North Sumatra Province to start practicing using Facebook or Instagram for product promotion.